Subjective memory complaints in Portuguese young adults: contributions from the adaptation of the prospective and retrospective memory questionnaire - Pereira, Diana R. (2018)
Self-report instruments that allow to characterize the frequency of daily memory failures are essential for a comprehensive assessment of memory functioning. In this context, we aimed to provide preliminary evidence of validity and reliability for the European Portuguese adaptation of the Prospective and Retrospective Memory Questionnaire (PRMQ). A total of 1052 healthy participants completed an online survey with the PRMQ. The exploration of the construct validity suggested the tripartite model with a general memory, a prospective memory, and a retrospective memory factors to have the best adjustment to the data. Measurement invariance across age and sex groups was also verified. The questionnaire revealed good convergent validity with a general self-report measure of memory (0.778 < r < 0.853), and satisfactory values of internal consistency (0.779 < Cronbach's alpha < 0.887) and of test-retest reliability (0.815 < r < 0.852). There were no prominent effects of sex and age in the PRMQ scores. Although the sample encompassed mainly younger and highly educated adults, this study presented the first evidence of validity and reliability for the European Portuguese version of the questionnaire.